Staff Performance in Small and Medium Enterprises as an impetus for economic growth in Kumasi Metropolis. - Daniel Ofori; Anthony Kusi; Edmond Oppong-Peprah; Benson Kwaku Nyarko; Grace Anning; Amankwah Edmond; Amatus Gyilbag (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study delved into the intricate relationships between staff /employee commitment, engagement, and SMEs performance within the organizational context. Using a sample of 100 participants, the study's extensive data was meaningfully analyzed following appropriate protocols through categorization and coding. The analysis was conducted using the Statistical Package for Social Science (SPSS) and Microsoft Excel. Correlation analysis was the principal statistical technique employed. The main goals of the study were to examine the relationships between commitment and engagement, commitment, and performance, as well as SMEs performance and economic growth. The findings unveiled significant positive correlations between all three dimensions, reinforcing the symbiotic nature of commitment, engagement, and performance. Specifically, greater degrees of commitment were found to be linked with increased engagement and superior performance outcomes. Similarly, greater engagement was associated with elevated performance levels. These results resonate deeply with existing literature, underscoring the pivotal role that commitment and engagement play in shaping staff /employee performance and SMEs growth for economic development. Moreover, the study offers practical recommendations for SMEs management to foster commitment, enhance engagement, and elevate performance within their organizations. The study also suggests potential avenues for future research, including longitudinal studies, cross-cultural analyses, and investigations into mediating and moderating factors. In conclusion, this study advances understanding of the intricate dynamics that bind staff /employee commitment, engagement, and performance, offering a foundation for further exploration and strategic implementation in SMEs settings to promote economic growth and development in Ghana.